1998
DOI: 10.1046/j.1365-2648.1998.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Preserving moral integrity: a follow‐up study with new graduate nurses

Abstract: The purpose of this follow-up study was to describe, explain and interpret how new graduate nurses perceived their adaptation to the 'real world' of hospital nursing and what they perceived as major influences on their moral values and ethical roles in the 2 years following graduation. The method was qualitative, specifically grounded theory. The earlier study took place when informants were senior nursing students. The follow-up study began after the informants had been practising for 1 year. Research questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
226
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(237 citation statements)
references
References 45 publications
10
226
0
1
Order By: Relevance
“…They stress the moral cost one pays by endorsing a role which is perceived as a safeguard but which actually undermines one's moral integrity. Kelly (1998Kelly ( , p. 1140 notices that as the nurses realised that they cannot practice at their high standards, and that they fail to be the nurses they aspired to be, they rationalized until they created a revised professional identity: "Coping with the loss of ideals requires that one justify why one no longer does what once was valued." However rationalization here is a form of self-deception and the resulting professional identity is a social construction rather than a reflection of the self (Kelly, 1998(Kelly, , p. 1140.…”
Section: Compartmentalization In the Workplacementioning
confidence: 99%
See 3 more Smart Citations
“…They stress the moral cost one pays by endorsing a role which is perceived as a safeguard but which actually undermines one's moral integrity. Kelly (1998Kelly ( , p. 1140 notices that as the nurses realised that they cannot practice at their high standards, and that they fail to be the nurses they aspired to be, they rationalized until they created a revised professional identity: "Coping with the loss of ideals requires that one justify why one no longer does what once was valued." However rationalization here is a form of self-deception and the resulting professional identity is a social construction rather than a reflection of the self (Kelly, 1998(Kelly, , p. 1140.…”
Section: Compartmentalization In the Workplacementioning
confidence: 99%
“…Kelly (1998Kelly ( , p. 1140 notices that as the nurses realised that they cannot practice at their high standards, and that they fail to be the nurses they aspired to be, they rationalized until they created a revised professional identity: "Coping with the loss of ideals requires that one justify why one no longer does what once was valued." However rationalization here is a form of self-deception and the resulting professional identity is a social construction rather than a reflection of the self (Kelly, 1998(Kelly, , p. 1140. Kelly (1998) concludes her study emphasizing the moral distress caused by a misrepresentation of the reality of the work environment by student nurses; however significant, this aspect should not overshadow the fact that the graduate nurses ultimately compromised their high moral ideals to fit into their ward.…”
Section: Compartmentalization In the Workplacementioning
confidence: 99%
See 2 more Smart Citations
“…Lachman (2007) posits that personal sacrifice is often accompanied by a sense of peace because the individual stood up for a nonnegotiable principle. Kelly (1998), however, found that the struggle of nurses to preserve their moral integrity resulted in moral stress. Another possible consequence of struggle is that it can elicit a reaction from opposing forces.…”
Section: Scientific Implicationsmentioning
confidence: 99%